Material Measures of Electrocaloric Cooling Power in Perovskite Ferroelectrics. Issue 8 (3rd July 2018) - Weyland, Florian; Perez‐Moyet, Richard; Rossetti, George A.; Novak, Nikola
Abstract: Many ferroelectric materials that can serve as refrigerants in electrocaloric cooling devices have been identified. To compare them, material measures of cooling power are useful. The electrocaloric performance characteristics of ferroelectric materials are determined to a large degree by the nature of the paraelectric to ferroelectric phase change, which influences the magnitude of the electrocaloric effect and the variation with temperature of the thermal conductivity and heat capacity. Here, those properties are compared for three promising ferroelectric materials. The materials chosen for study have differing phase change characteristics ranging from first‐order to diffuse/relaxor‐like behavior, and include barium titanate and lead magnesium niobate—lead titanate single crystals and polycrystalline barium zirconate‐titanate ceramics. Using measured thermophysical property data, and a simple model based on the Newtonian cooling of a thin plate, the dependences of the material cooling power on the dimensionless temperature, characteristic distance, and holding time for heat transfer are determined. Relationships existing between material cooling power and the nature of the phase transition, thermophysical properties, and the electrocaloric behavior are illustrated. Although device‐level factors, such as thermal resistances at electrode interfaces are ignored, the results suggest a simple basis of comparison for electrocaloric materials. Abstract : Material figures of merit are useful for comparing ferroelectrics as electrocaloric refrigerants in different device configurations. An equation is developed that provides a material measure of electrocaloric cooling power. The influence of thermophysical properties and electrocaloric behavior for ferroelectric materials with differing phase transition characteristics is illustrated.